ANALISIS TENTANG PENYELESAIAN SENGKETA WARIS PADA MASYARAKAT BATAK TOBA DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Simamora, A Sandro; Erlinda, Sri; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstracts : This research was motivated by the inheritance disputes that occur in society Batak Toba Mandau sub Bengkalis. Caused by the erosion of a sense of family kinship, especially in Batak society. As an alternative solution used is through the Act, namely Consulting, Negotiation, Mediation, Conciliation and Artbitrase and through Customary Law ie Marhata (family council) and the Institute of Traditional. The problem of this research is How the Inheritance Dispute Resolution In Batak Toba Society Saber In District Bengkalis? The purpose of this study is to explain the Community Dispute Resolution Waris Batak Toba Saber In District Bengkalis. The study population was Batak Toba people who have had disputes of inheritance amounted to 23 people, indigenous leader 1 and the sample was 24 people. Data collection instruments which the questionnaire consists of 34 questions. Analysis of data using qualitative descriptive analysis. These results indicate that the community Batak Toba Mandau sub Bengkalis in resolving disputes and inheritance seen from the percentage 24 as much as 28.13% of respondents categorized rarely use the Act, whereas 58.34% are categorized often use Customary Law with the highest percentage 54.17 % by respondents as many as 13 respondents using Marhata way (the family council).Keywords: Inheritance dispute,community batak toba